Multi-band antennas for ITS applications - Shang, Yuxin (2017)
Transportation comprises an essential part in modern society and an intelligent transportation system (ITS) is promoting people’s daily life as it provides faster, safer, more environmental and economic friendly strategies for transportation. ITS may be used to help the driver detect the anterior pedestrians to help the driver take actions early and prevent traffic accidents. Under extreme weather such as heavy fog or rain, the intelligent transportation system may also alert the drivers to the potential danger ahead. Communication technologies are widely used in ITS as it is necessary for vehicles to get connect to everything around and this is called a V2X (vehicle-to-everything) system. To achieve this communication connection, antennas are required to transmit and receive radio waves and signals. This project aims to design an antenna for ITS applications. The operational frequency requirement of this antenna is 0.69GHz to 0.96GHz to and 1.7GHz to 2.7GHz, which satisfies the LTE (long-term evolution) usage. The antenna should be omni-directional as the vehicle should have the ability to transmit and receive signals from all directions to ensure safety. The lower frequency band is a narrow band comparing to the higher frequency band, so a microstrip monopole antenna with triangular top is proposed to reach the wide-band requirement, and a L-shaped strip is added onto the triangle to generate the lower frequency band. In contrast, a microstrip monopole antenna with inverted triangular top and a L-shaped strip is also design and simulated to make comparison with the previous design. The antenna bandwidth, radiation pattern, antenna gain and input impedance parameters are analyzed to evaluate the performance. Eventually, the proposed antenna designs are fabricated and measured in the laboratory to conclude if they meet the requirements in ITS applications.